KEADAAN JALAN DI DAERAH HUTAN NON-JATI JAWA TENGAH DAN POTENSINYA DALAM AKSELERASI EROSI TANAH - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
An investigation on forest road conditions in non-teak forests of Kedu Utara and kedu selatan Forest Districts and their soil erosion potentials was conducted in early 1992. The samples of roads investigated were 6 segments in kedu Utara and other 6 segments in Kedu selatan in Kedu Selatan, each of 50 m long, Forest areas distribution and road inventory were also investigated and collected. It is found that forest sections in both forest districts are spread in several regencies and each section consisted of several relative small areas scattered in many locations which are seperated by villages and other land uses. This condition becomes the constraint in practicing good forest management in the area. The total area used for rood infrastructure (combined graveled forest roads and public roads) in Kedu utara and kedu selatan are 8.30 ha (0.03%) and 60.62 ha (0.14%) respectively. This means that an average land lost due to roading is only 0.08%.All factors in the universal soil loss equation (USLE) for the non- teak forest areas of kedu utara and kedu selatan are in the level of high scores in terms of soil erosion acceleration potential. It is noticed in the field that many segments of forest roads have been seriously eroded, especially along the berms and ditches, and on the fill and cut sections. Better planning and construction practices of forest roads are necessary to avoid forest land damage due to soil erosion.